Rendszerfüggő lexika - Tóth Szergej (Tudományos és művészeti műhelymunkák: új utakon a Pedagógusképző Kar című konferencia előadásai, 2009)
The author looks back the issues of his research carried out ten years ago with the contribution of a team named New democracies and human communication who functioned within an International scientific project entitled Language in a Post-totalitarian Society. One of the outcomes of their research was that „the Hungarian society was not ready at that timе to create and use Street signs and names of public places free from ideoiogies”. Bearing this view in our mind we can observe that there has been a tendency recently to rename streets being generated by political ambitions.